2021
DOI: 10.1186/s13104-021-05594-9
|View full text |Cite
|
Sign up to set email alerts
|

Arylated gold nanoparticles have no effect on the adipogenic differentiation of MG-63 cells nor regulate any key signaling pathway during the differentiation

Abstract: Objective MG-63 cells that have osteoblastic and adipogenic differentiation potential were evaluated for internalization, and adipogenic differentiation in the presence and absence of the covalently functionalized aryl gold nanoparticles (AuNPs-C6H4-4-COOH). Results Inductively coupled plasma, flow cytometry and confocal microscopy analyses confirmed that gold nanoparticles were easily internalized by MG-63 cells. The MG-63 cells were differentiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The labeling of MG-63 cells with AuNPs in previous studies ( 34 , 35 ) reported no significant effects on the cellular cycle or key signaling pathways after labeling with up to 40µM AuNPs, consistent with our results. Steckiewicz et al ( 36 ) reported that high cell viability exceeding 95% was observed in MG-63 cell labeling with concentrations of up to 5µg/mL of spherical AuNPs, whereas our study demonstrated 96.18% viability even at concentrations of up to 100µg/mL, representing a mere 3.82% compromise in viability.…”
Section: Discussionsupporting
confidence: 92%
“…The labeling of MG-63 cells with AuNPs in previous studies ( 34 , 35 ) reported no significant effects on the cellular cycle or key signaling pathways after labeling with up to 40µM AuNPs, consistent with our results. Steckiewicz et al ( 36 ) reported that high cell viability exceeding 95% was observed in MG-63 cell labeling with concentrations of up to 5µg/mL of spherical AuNPs, whereas our study demonstrated 96.18% viability even at concentrations of up to 100µg/mL, representing a mere 3.82% compromise in viability.…”
Section: Discussionsupporting
confidence: 92%
“…For example, arylated AuNPs did not mediate the adipogenic differentiation of MG-63 cells or regulate any key signalling pathway during their differentiation. 79 In summary, ligands with diverse charge and chemical characteristic can exert a decisive influence on their osteogenic property.…”
Section: Surface Chemistry and Surface Topographymentioning
confidence: 99%
“…Additionally, AuNPs could potentially aid in the study of genetic diseases. As was already indicated, substantial research on the absorption of important signaling pathways using MG-63 cells with gold–aryl NPs has been conducted by Abdulwahab et al [ 127 ]. They suggested that these particles may be suitable for drug delivery and tracing studies during development.…”
Section: Gene Silencingmentioning
confidence: 99%